How to Supervise Education? To Develop Teachers to Manage Learning to Meet the Full Potential of Quality Learners - Sukhamsri, Chadawan; Unkong, Thidawan (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
As education in the modern world increasingly adopts new learning management systems and technologies, it is imperative that teachers are provided with the support and development necessary to effectively use these tools and improve student learning. This article presents an approach to teacher supervision for developing new learning management systems through the creation of professional learning communities (PLC) by establishing shared vision and goals. In addition, a coaching-based supervision approach is another approach that can enhance teacher development potential, starting with the establishment of a trusting relationship between the coach and teacher, providing continuous observation, support, and engaging teachers in a collaborative conversation. This comprehensive teacher supervision approach is essential for developing learning processes for developing educators and preparing students for success in order to develop learners to their full potential.